Reabilitação de pacientes com implantes osseointegrados pelo sistema IOL® acompanhamento clínico de cinco anos - Rabelo, Viviane de Azevedo (2008)
The objective of this work was to evaluate mandibular rehabilitation using the IOL system comprising an acrylic resin, fixed implant-supported prosthesis without metal framework over a 5-year follow-up period osseointegrated. The sample was composed of 12 totally edentulous patients who received five implants each in the anterior mandibular region between the mental foramina, with lengths varying between 10.0mm and 18.0mm and diameters of 3.75mm and 4.0mm. A fixed prosthesis was immediately delivered over these implants using the patient s pre-existing conventional total prosthesis and specific prosthetic components from the IOL system. Two quality of life questionnaires (OHIP and VAS) were used with the aim to evaluate the relationship between the IOL system and quality of life from the patients own point of view. The clinical behavior of fixed prosthesis was evaluated by measuring possible alterations in the ISQ values of the implants over the 5-year follow-up period to check its influence on the stability of the bone-implant interface. Biologic and mechanical complications on the IOL system were also related. y. Based on the responses provided in the questionnaires, the patients declared themselves to be very satisfied with the rehabilitations received. The resonance frequency analysis indicated a high degree of primary implant stability resulting in very favorable conditions for osseointegration. Comparisons between the values obtained during the follow-up periods indicated a reduction in the stability of the implants from the moment of installation (average ISQ value = 73.28) until the end of the fourth month (average ISQ value =71.94), followed by an increase at the end of the twelfth month (average ISQ 73.12) with a stabilization at twenty four months (average ISQ value = 73.08) and a reduction when the prosthesis had been in function for sixty months (average ISQ value = 71.88). The maintenance of bone architecture around implants was verified by panoramic radiographic examining. It is therefore possible to conclude that, despite some complaints by certain patients, all of them were satisfied with the treatment offered. Based on the questionnaires used, it may be stated that rehabilitation with implants in these patients provide them benefits beyond the oral cavity, positively affecting their quality of life. There were no statistically significant differences between the resonance frequency analysis values after sixty months in function, when compared to baseline values. Based on the prosthetic failures found after five years in function, we must consider the provisional character of thistype of prosthetic rehabilitation.